Evolution of wheat architecture, physiology, and metabolism during domestication and further cultivation - Katamadze, Arturs (2023)
Funding Information: Artūrs Katamadze, Omar Vergara-Díaz, Estefanía Uberegui, Ander Yoldi-Achalandabaso and Rubén Vicente acknowledge the support of Fundação para a Ciência e a Tecnologia (FCT, Portugal), through the GREEN-IT – Bioresources for Sustainability R&D Unit (UIDB/04551/2020, UIDP/04551/2020) and the LS4FUTURE Associated Laboratory (LA/P/0087/2020). Rubén Vicente was also funded by FCT through the Program ‘Concurso de Estímulo ao Emprego Científico Institucional’ (CEECINST/00102/2018/CP1567/CT0039). José Luis Araus acknowledges the support from ICREA Acadèmia, Generalitat de Catalunya, and the project PID2019-106650RB-C21 from the Ministerio de Ciencia e Innovación, Spain. Publisher Copyright: © 2023 Crop Science Society of China and Institute of Crop Science, CAAS